2015
DOI: 10.1103/physrevlett.115.197701
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Lifetime Paradoxically Enhanced by Dissipation and Decoherence: Toward Efficient Energy Conversion of a Solar Cell

Abstract: Energy dissipation and decoherence are at first glance harmful to acquiring the long exciton lifetime desired for efficient photovoltaics. In the presence of both optically forbidden (namely, dark) and allowed (bright) excitons, however, they can be instrumental, as suggested in photosynthesis. By simulating the quantum dynamics of exciton relaxations, we show that the optimized decoherence that imposes a quantum-to-classical crossover with the dissipation realizes a dramatically longer lifetime. In an example… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Dark state protection can only be significant in systems where radiative recombination is the dominant loss mechanism [16,[27][28][29][30][31][32]. This is not the case, for example, in photosynthetic systems, where recombination is predominantly non-radiative [10,24,37,38] and mostly unaffected by transition dipole magnitudes.…”
Section: Type I Enhancementsmentioning
confidence: 99%
“…Dark state protection can only be significant in systems where radiative recombination is the dominant loss mechanism [16,[27][28][29][30][31][32]. This is not the case, for example, in photosynthetic systems, where recombination is predominantly non-radiative [10,24,37,38] and mostly unaffected by transition dipole magnitudes.…”
Section: Type I Enhancementsmentioning
confidence: 99%
“…Recently, many theoretical studies have suggested that noise-induced quantum coherence [ 2 , 3 ], Fano-induced coherence [ 4 ] or delocalized quantum states of interacting dipoles [ 5 , 6 , 7 , 8 ] can reduce the radiative recombination loss of a solar cell, thus enhancing the efficiency of solar cells. The same idea is applied to the photosynthetic complex [ 9 , 10 , 11 , 12 ]. Most of these studies employ the donor-acceptor quantum photocell model where the donor is in thermal equilibrium with a hot bath, that is, the sun at and the acceptor is at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many theoretical studies have suggested that noise-induced quantum coherence [2,3], Fano-induced coherence [4] or delocalized quantum states of interacting dipoles [5][6][7][8] can reduce the radiative recombination loss of a solar cell, thus enhancing the efficiency of solar cells. The same idea is applied to the photosynthetic complex [9][10][11][12]. Most of these studies employ the donor-acceptor quantum photocell model where the donor is in thermal equilibrium with a hot bath, i.e., the sun at 5800 K and the acceptor is at room temperature.…”
Section: Introductionmentioning
confidence: 99%